Augmentation and vocal fold biomechanics in a recurrent laryngeal nerve injury model. Issue 4 (6th July 2022) - Miar, Solaleh; Walters, Benjamin; Gonzales, Gabriela; Malka, Ronit; Baker, Amelia; Guda, Teja; Dion, Gregory R.
Abstract: Objectives/hypothesis: Composite vocal fold (VF) biomechanical data are lacking for augmentation after recurrent laryngeal nerve (RLN) injury. We hypothesize resulting atrophy decreases VF stiffness and augmentation restores native VF biomechanics. Methods: Sixteen Yorkshire Crossbreed swine underwent left RLN transection and were observed or underwent carboxymethylcellulose (CMC) or calcium hydroxyapatite (CaHa) augmentation at 2 weeks. Biomechanical measurements (structural stiffness, displacement, and maximum load) were measured at 4 or 12 weeks. Thyroarytenoid (TA) muscle cross‐sectional area was quantified and compared with two‐way ANOVA with Tukey's post hoc test. Results: After 4 weeks, right greater than left structural stiffness (mean ± SE) was observed (49.6 ± 0.003 vs. 28.4 ± 0.002 mN/mm), left greater than right displacement at 6.3 mN (0.54 ± 0.01 vs. 0.46 ± 0.01 mm, p < .01) was identified, and right greater than left maximum load (72.3 ± 0.005 vs. 40.8 ± 0.003 mN) was recorded. TA muscle atrophy in the injured group without augmentations was significant compared to the noninjured side, and muscle atrophy was seen at overall muscle area and individual muscle bundles. CMC augmentation appears to maintain TA muscle structure in the first 4 weeks with atrophy present at 12 weeks. Conclusions: VF biomechanical properties match TA muscle atrophy in this model, and both CMC and CaHa injection demonstrated improved biomechanical properties and slower TA atrophy compared to the uninjured side. Taken together, these data provide a quantifiable biomechanical basis for early injection laryngoplasty to improve dysphonia and potentially improve healing in reversible unilateral vocal fold atrophy. Level of evidence: N/A Abstract : We found that in vocal fold biomechanical properties match thyroarytenoid (TA) muscle atrophy after recurrent laryngeal nerve transection over time. While both carboxymethylcellulose (CMC) and calcium hydroxyapatite (CaHa) increase vocal fold stiffness after denervation, this effect diminishes with time and does not alter TA atrophy. CMC injection appears to achieve vocal fold biomechanical properties closest to native vocal fold tissue and have these properties persist longer than CaHa.